Lymphatic Filariasis in Southwestern Nigerian Rural Communities: A Cross-sectional Survey of the Knowledge, Awareness, and Predisposing Factors - Bolatito Oluwabiyi; Oyetunde T. Oyeyemi; Adetayo Olorunlana; Nofisat Omiyeniyi; Ayomide Koleosho (Ubiquity Press, 2017)
Background Nigeria is the second most endemic country in the world for lymphatic filariasis, with control efforts often hampered by poor community awareness and involvement in intervention strategies. Objective The aim of this study was to assess the knowledge, perception, and psychosocial aspects of some residents in Nigerian rural communities about lymphatic filariasis in order to develop disease control and intervention strategies with active community involvement. Methods A standardized questionnaire was adapted and a scale of measurement was developed. The methodology was quantitative and the study design was cross-sectional. A sample of 203 respondents was selected using a precision of 0.06. Findings A majority (51.2%) had heard of elephantiasis but very few (9.3%) had accurate knowledge of the causes of the disease. Most people (53.2%) had no sources of information about elephantiasis, and of the few individuals that claimed availability of sources of information, information about the mode of transmission of the disease (10.0%) was the most common. Very few individuals (7.9%) believed mosquitoes were associated with elephantiasis, with 16.7% having a history of elephantiasis. The proportion of respondents who did not use mosquito netting (61.1%) was significantly higher than those who did use it (33.0%) ('P' < .05). An appreciable proportion (26.1%) of individuals believed elephantiasis to be an abominable disease, with 5.9% individuals believing that people treat the victims of elephantiasis with disrespect. Conclusions The study areas are at high risk of lymphatic filariasis. There is a need to create a knowledge-based awareness among the residents for effective management of the disease.